Nicotine estimations in electronic cigarette e-liquids among Malaysian marketed samples - Rahman, Azizur; Nik Mohamed, Mohamad Haniki; ., Syed Mahmood (Taylor and Francis, 2018)
E-cigarette (e-cig) is becoming a popular substitute for tobacco cigarette all over the world. The chief constituents of e-cig e-liquids are nicotine, propylene glycol, glycerine, and a couple of other flavouring constituents. The current study objective was to find out the discrepancy in the labelled vs actual nicotine concentration amid the Malaysian marketed e-liquids brands for consumer safety purpose. The study examined the 69 e-liquids samples that were selected from Malaysia market. The nicotine estimation was measured by Agilent 6890N Gas chromatography-mass spectrometry with 5973 mass selective detector (MSD). Out of 69 samples analysed for actual nicotine level, in 64 samples nicotine concentration was found to be as low from - 1 to -67.13 % and in remaining 5 samples it contained higher from +2.8 to +24.70. A total of 60 (86.9 %) samples were found to have significant discrepancies in labelled vs. actual nicotine concentration. The study concludes that high discrepancy in the labelled vs actual nicotine concentration was found among the Malaysian marketed e-liquids brands. Based on analysis results, there is an urgent need for regulation for these marketed nicotine eliquids products in Malaysia. The study suggests that corresponding Malaysian tobacco regulatory authorities should instruct suppliers of e-liquids for flawless packaging for consumer safety reason.